Demographic Profile of Liver Injury Managed at a Tertiary Care Hospital in Central Nepal -A Retrospective Study - Belbase, Narayan Prasad; Jalan, Aditya Kumar; Upadhyay, Hari; Mishra, Rohit; Karki, Mukesh; Kumar, Sujit (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: The liver is one of the commonly injured solid organ following abdominal trauma. The aim of this study was to determine the outcome of liver injuries managed operatively or non-operatively and predict factors affecting morbidity and mortality. Materials & Methods: This was a retrospective study of 40 liver injuries managed in the department of Surgical Gastroenterology at College of Medical Sciences over a period of 2 years. The liver injury was classified in accordance with the American Association for the Surgery of Trauma liver injury scoring scale. Patients were divided into two groups those managed operatively or non-operatively and were compared in terms of demographic profile and outcome. Results: Forty patients were analyzed. The mean age of the patients was 29.95years. Male predominance was seen with 72.5% of the cases. Road traffic accidents were the commonest mode of injury seen in 72.5% cases. The mean Revised Trauma Score (RTS) and Injury severity score (ISS) were 7.11and 22.58. The mean systolic BP, hospital stay and ICU stay were 93.80 mm of mercury, 11.55 days and 3.55 days respectively. Twenty six patients (65%) were initially managed non-operatively and 14 patients were managed operatively. Five patients had to be converted to operative management for hemodynamic instability. Mortality was 7.6% in patient undergoing non-operative management and 21.43% in patients managed operatively. Low systolic BP at presentation, low RTS score, high ISS score, high AST, ALT and prothrombin time were significantly associated with operative management and mortality. Conclusion: Patients with hemodynamic instability, low RTS score, high ISS score, high liver enzymes have high likelihood of operative management.